2025年2月4日 星期二

多項式,求未定係數

 

GPT Icon

Given Equation

2x34x25x+1=a(x1)(x+2)(x+3)+b(x1)(x2)(x3)+c(x+2)(x3)(x+1)2x^3 - 4x^2 - 5x + 1 = a(x - 1)(x + 2)(x + 3) + b(x - 1)(x - 2)(x - 3) + c(x + 2)(x - 3)(x + 1)

We will substitute three specific values of xx to solve for a,b,ca, b, c.


Step 1: Substituting x=1

Since (x1)=0, the terms involving aa and b vanish, leaving:

f(1)=c(1+2)(13)(1+1)f(1) = c(1 + 2)(1 - 3)(1 + 1)

Compute f(1):

2(1)34(1)25(1)+1=245+1=62(1)^3 - 4(1)^2 - 5(1) + 1 = 2 - 4 - 5 + 1 = -6

Compute the right-hand side:

c(3)(2)(2)=12cc(3)(-2)(2) = -12c

Thus, we solve:

6=12c-6 = -12c
c=12c = \frac{1}{2}


Step 2: Substituting x=2

Since (x+2)=0, the terms involving aa and cc vanish, leaving:

f(2)=b(21)(22)(23)f(-2) = b(-2 - 1)(-2 - 2)(-2 - 3)

Compute f(2)f(-2):

2(2)34(2)25(2)+12(-2)^3 - 4(-2)^2 - 5(-2) + 1
=2(8)4(4)5(2)+1= 2(-8) - 4(4) - 5(-2) + 1
=1616+10+1=21= -16 - 16 + 10 + 1 = -21

Compute the right-hand side:

b(3)(4)(5)=60bb(-3)(-4)(-5) = -60b

Thus, we solve:

21=60b-21 = -60b
b=720b = \frac{7}{20}


Step 3: Substituting x=3

Since (x3)=0, the terms involving bb and cc vanish, leaving:

f(3)=a(31)(3+2)(3+3)f(3) = a(3 - 1)(3 + 2)(3 + 3)

Compute f(3)f(3):

2(3)34(3)25(3)+12(3)^3 - 4(3)^2 - 5(3) + 1
=2(27)4(9)15+1= 2(27) - 4(9) - 15 + 1
=543615+1=4= 54 - 36 - 15 + 1 = 4

Compute the right-hand side:

a(2)(5)(6)=60aa(2)(5)(6) = 60a

Thus, we solve:

4=60a4 = 60a
a=115a = \frac{1}{15}


Final Answer

a=115,b=720,c=12\boxed{a = \frac{1}{15}, \quad b = \frac{7}{20}, \quad c = \frac{1}{2}}

This is the correct set of values for a,b,ca, b, c. 😊

沒有留言:

張貼留言